Long bone human anlage longitudinal and circumferential growth in the fetal period and comparison with the growth plate cartilage of the postnatal age. Issue 3 (23rd December 2018) - Pazzaglia, Ugo E.; Reguzzoni, Marcella; Casati, Lavinia; Minini, Andrea; Salvi, Andrea G.; Sibilia, Valeria
Abstract: The patterns of longitudinal and peripheral growth were analyzed in human autopod cartilage anlagen (fetal developmental stage 20th–22nd week) through morphometric assessment of chondrocyte parameter size, shape, alignment and orientation between peripheral and central sectors of the anlage transition zone defined by primary ossification center and the epiphyseal basis. The aim was to correlate the chondrocyte dynamics with the longitudinal and peripheral growth. A further comparison was carried out between the corresponding sectors of the postnatal (3–5 months old) growth plate cartilage documenting: (1) the different chondrocyte framework and the new peripheral mechanism; (2) the opposite direction of fetal periosteal ossification versus the Lacroix bone bark. Measurement of multiple parameters (% lac area, % total matrix area, total lac density and mean single lac area), which characterize the cartilage Anlage growth, suggested the following correlations with chondrocyte duplication rate: (a) slow duplication rate ≈ coupled, intralacunar chondrocytes (in central epiphysis); (b) repeated/frequent cell duplications ≈ clusters (in the basal epiphyseal layer); (c) clusters of chondrocytes before becoming hypertrophic were stacked up on the top of each other (both in the Anlage transition zone or in the columns of metaphyseal growth plate); (d) enhanced osteoclastic resorption of the Lacroix bone bark lower end, extended to the more external metaphyseal trabeculae counterbalancing the discrepancy between the epiphyseal and the diaphyseal circumferential growth. Abstract : Light microscopy morphometry of cartilage lacunae in fetal anlagen and the consequent chondrocyte organization in the postnatal growth plate cartilage were examined in the development of human bones. Zonal patterning analysis suggested a correlation with the peripheral cartilage matrix apposition and the intralacunar chondrocyte duplication rate.